The predictive value of free thyroxine combined with tubular atrophy/interstitial fibrosis for poor prognosis in patients with IgA nephropathy - Yang, Bixia; Zhou, Wen; Cui, Liqin; Tian, Li; Ni, Yanhong; Yang, Min; Yang, Yan (Frontiers in Endocrinology, 2024)
Background: IgA nephropathy (IgAN), the most common type of glomerulonephritis, has great individual differences in prognosis. Many studies showed the relationship between thyroid hormones and chronic kidney disease. However, the relationship between free thyroxine (FT4), as a thyroid hormone, and IgAN is still unclear. This study aimed to evaluate the impact of FT4 on IgAN prognosis.: This retrospective study involved 223 patients with biopsy-proven IgAN. The renal composite outcomes were defined as: (1) ESRD, defined as eGFR < 15 ml/(min•1.73 m 2 ) or initiation of renal replacement therapy (hemodialysis, peritoneal dialysis, renal transplantation); (2) serum creatinine doubled from baseline; (3) eGFR decreased by more than 50% from baseline. The predictive value was determined by the area under the curve (AUC). Kaplan-Meier and Cox proportional hazards analyses assessed renal progression and prognosis.Results: After 38(26-54) months of follow-up, 23 patients (10.3%) experienced renal composite outcomes. Kaplan-Meier survival curve analysis showed that the renal survival rate of the IgAN patients with FT4<15.18pmol/L was lower than that with FT4 ≥15.18pmol/L (P < 0. 001). Multivariate Cox regression model analysis showed that FT4 was a protective factor for poor prognosis of IgAN patients, whether as a continuous variable or a categorical variable (HR 0.68, 95%CI 0.51-0.90, P =0.007; HR 0.04, 95%CI 0.01-0.20, P <0.001). ROC curve analysis showed that FT4 combined with t score had a high predictive value for poor prognosis of IgAN patients (AUC=0.881, P<0.001).FT4 was a protective factor for IgAN. In addition, FT4 combined with tubular atrophy/interstitial fibrosis had a high predictive value for poor prognosis of IgAN.